Safe generation and use of bromine azide under continuous flow conditions – selective 1, 2-bromoazidation of olefins. Issue 3 (9th December 2015) - Cantillo, David; Gutmann, Bernhard; Oliver Kappe, C.
Abstract : Hazardous bromine azide (BrN3 ) can be safely generated and reacted with olefins in a continuous flow reactor under irradiation with light. Abstract : Bromine azide (BrN3 ), a useful but extremely toxic and explosive reagent for the preparation of vicinal 1, 2-bromine azide compounds, was safely generated and reacted in situ with alkenes in a continuous flow photoreactor. BrN3 was generated by a novel procedure from NaBr and NaN3 in water, and efficiently extracted into an organic phase containing the alkene thus avoiding decomposition. The resulting addition products have been used for the preparation of several useful building blocks.